The Facilitating Act Framework: A new insight into cultural ecosystem services through investigating women, wild swimming and community - Lucy Barnard; Seb O'Connor; Klaus Glenk (People and Nature)
Abstract We present the Facilitating Act Framework (FAF) as a way to challenge more linear ways of thinking about cultural ecosystem services. The framework moves towards more relational and participant‐led processes to provide insights on how values emerge through engaging with nature. The FAF has three pillars: (i) participant autonomy, (ii) open‐ended parameters, and (iii) focusing on processes over outcomes. We the FAF to a case study of women and wild swimming in Scotland, illustrating how each of the pillars can be applied in practice using a mixed methods approach with a Q methodology element at its core. We identify four factors, the ‘competitive edge’, ‘connection‐to‐nature seekers’, ‘sharers and carers’ and ‘enablers’ that variously characterised what was important to women when they participated in the ‘act’ of wild swimming. This case study revealed the importance of community and the key social dynamics through which values emerged and connected people to nature, pointing to a range of better targeted possible policy interventions. The FAF offers an avenue to deepen our understanding of how values emerge through interactions with nature as a way to better embed relational thinking in the context of cultural ecosystem services. Read the free Plain Language Summary for this article on the Journal blog.